BEHIND-THE-SCENES MASKS: FACTORS WHICH ENCOURAGES USERS TO FAKE ACCOUNTS ON SOCIAL MEDIA X - Naisya Insani Ramadani; Salwa Laila Ayu Budiman; Ririn Maesaroh; Mirna Nur Alia Abdullah (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
This study aims to analyze the factors that encourage the use of fake accounts on social media X (Twitter) as part of digital social interaction practices. The research employs a descriptive quantitative approach, with data collected through a Likert-scale questionnaire distributed to active users who have used anonymous accounts. The results indicate that fake account usage is influenced by the need for security, the desire for freer self-expression, and the influence of digital environments where such practices are considered normal. Anonymous accounts are utilized to avoid social judgment, maintain real-life relationships, and provide alternative spaces for sharing personal experiences. These findings suggest that anonymity is not merely a technical condition but a social strategy for managing digital identity and adapting to the dynamics of online interaction